Hälsningsfrasers sociala värde i sverigesvenskt och finlandssvenskt talspråk - Jenny Nilsson; Catrin Norrby; Jan Lindström; Camilla Wide (Kungl. Gustav Adolfs Akademien för svensk folkkultur i samarbete med Institutet för språk och folkminnen, 2022)
Swedish is a pluricentric language and has official status in both Sweden and Finland. Until recently, most studies on such languages have focused on differences and similarities in grammar and lexicon, and less on pragmatic variation. We suggest that a pragmatic perspective is of help in understanding the relationship between national varieties, and in this study we investigate greetings in Sweden Swedish and Finland Swedish. Previous comparisons of the two varieties suggest that Sweden Swedish is less formal than Finland Swedish, and in this article we problematise the concept of formality and discuss whether formality could explain any differences in the use of greetings. We use three data sets from each of the two countries: videorecorded service encounters from box offices and information desks, recorded focus groups, and experiments. Combined, the data suggest that the Finland-Swedish greeting repertoire is larger than the Sweden-Swedish one, and that Swedish speakers in Finland are therefore more sensitive to social distance than their counterparts in Sweden. At the same time, the study highlights the complexity in the use of greetings, and shows that variables such as gender, age, context and degree of acquaintance all play an important part in the use of greetings in both Sweden Swedish and Finland Swedish.